1994
DOI: 10.1111/j.1365-2265.1994.tb01820.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgen suppressive effect of GnRH agonist in ovarian hyperthecosis and virilizing turnours*

Abstract: In virilized women, the findings of increased serum testosterone with normal gonadotrophin levels and GnRHa suppression of gonadotrophins leading to normalization of testosterone levels, suggest that various ovarian androgen-secreting tumours, as well as hyperthecosis, are not autonomous but apparently depend upon continuous gonadotrophin stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…On the other hand, DHEAS may be decreased in the case of sulphatase enzyme defect and in adrenocortical cancer. In ovarian tumours, raised testosterone may be LH-dependent and in some cases can be suppressed by treatment with gonadotrophin-releasing hormone (GNRH) agonist, oestrogen-progestogen or cyproterone acetate (CPA) (70). However, it should be noted that hyperthecosis and ovarian androgen-secreting tumours are both LH-dependent and therefore should be further explored by complementary imaging (71).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…On the other hand, DHEAS may be decreased in the case of sulphatase enzyme defect and in adrenocortical cancer. In ovarian tumours, raised testosterone may be LH-dependent and in some cases can be suppressed by treatment with gonadotrophin-releasing hormone (GNRH) agonist, oestrogen-progestogen or cyproterone acetate (CPA) (70). However, it should be noted that hyperthecosis and ovarian androgen-secreting tumours are both LH-dependent and therefore should be further explored by complementary imaging (71).…”
Section: Laboratory and Biomarkersmentioning
confidence: 99%
“…The performance of a 2-to 5-day low-dose dexamethasone suppression test has been suggested, but this approach has not been studied for hyperandrogenism in postmenopausal women (20). Finally, there are small and contradictory results concerning the discriminatory effect of gonadotropin suppression in the evaluation of postmenopausal hyperandrogenism (12,21). Immunohistochemical analysis is not directly involved in discriminating tumor lesions from nontumor pathology but has already been used to elucidate the mechanism of an ovarian tumoral hyperandrogenism (22).…”
Section: Introductionmentioning
confidence: 99%
“…Gonadotropin has been known to suppress androgen secretion by ovarian virilizing tumor. Pascal et al13 suggested that various ovarian androgen-secreting tumors, as well as hyperthecosis, were not autonomous but apparently depended upon continuous gonadotropin stimulation. Imai et al14 also noted a direct suppressive effect of GnRHa on ovarian steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%